2014
DOI: 10.1371/journal.pone.0103785
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Social Capital Questionnaire for Adolescent Students (SCQ-AS)

Abstract: ObjectivesSocial capital has been studied due to its contextual influence on health. However, no specific assessment tool has been developed and validated for the measurement of social capital among 12-year-old adolescent students. The aim of the present study was to develop and validate a quick, simple assessment tool to measure social capital among adolescent students.MethodsA questionnaire was developed based on a review of relevant literature. For such, searches were made of the Scientific Electronic Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 42 publications
3
85
0
1
Order By: Relevance
“…One study revealed protective contextual effects on dental caries [Patussi et al, 2006a], whereas others found a lack of association between SC and oral dental trauma [Moyses et al, 2006;de Paiva et al, 2015]. SC in schools is an emerging topic of SC research of contemporary behavioural epidemiology, since children spend many hours in a school environment [Eriksson et al, 2012;Paiva et al, 2014], and contextual factors at school, such as physical school structure and social environment, may influence the health and well-being of children [Moyses et al, 2003;Kwan et al, 2005]. There is evidence that an unfavourable physical environment in schools can contribute to a lower quality of oral health [Moyses et al, 2003], higher accident rates [Malikaew et al, 2003;Patussi et al, 2006] and worse academic performance of students [Kwan et al, 2005].…”
mentioning
confidence: 99%
“…One study revealed protective contextual effects on dental caries [Patussi et al, 2006a], whereas others found a lack of association between SC and oral dental trauma [Moyses et al, 2006;de Paiva et al, 2015]. SC in schools is an emerging topic of SC research of contemporary behavioural epidemiology, since children spend many hours in a school environment [Eriksson et al, 2012;Paiva et al, 2014], and contextual factors at school, such as physical school structure and social environment, may influence the health and well-being of children [Moyses et al, 2003;Kwan et al, 2005]. There is evidence that an unfavourable physical environment in schools can contribute to a lower quality of oral health [Moyses et al, 2003], higher accident rates [Malikaew et al, 2003;Patussi et al, 2006] and worse academic performance of students [Kwan et al, 2005].…”
mentioning
confidence: 99%
“…However, no such scales have been available in Japan. Therefore, in the present study, the authors investigated the cultural adaptation and psychometric properties of the Social Capital Questionnaire for Adolescent Students (SCQ‐AS) among Japanese students.…”
Section: Factor Loadings Of 12 Items Of the Japanese Version Of The Smentioning
confidence: 99%
“…The SCQ‐AS is a self‐rating 12‐item questionnaire developed by researchers in Brazil . The items of the SCQ‐AS and details about its scale development study (reliability, factor structure) are listed in Appendices S1 and S2.…”
Section: Factor Loadings Of 12 Items Of the Japanese Version Of The Smentioning
confidence: 99%
See 2 more Smart Citations